OB Simulation During the COVID-19 Pandemic. Issue 5 (September 2021) - DiCioccio, Heather Condo
Abstract : Conducting simulations in the hospital setting has been challenging during the COVID-19 pandemic due to safety restrictions to minimize risk of viral transmission and due to perinatal health care workers, such as nurses, midwives, and obstetricians needed in direct care, with little to no time for educational activities. Our guest columnist, Dr. DiCioccio, a perinatal nursing professional development specialist, covers alternatives to in-person OB simulation that are designed to meet The Joint Commission standards for maternal safety.